1992
DOI: 10.1111/j.1439-0442.1992.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tamm‐Horsfall Glycoprotein Concentrations in Normal and Urolithiasis‐Affected Male Cats Determined by an ELISA

Abstract: Summary A precise and reproducible enzyme‐linked immunosorbent assay (ELISA) which measures urinary cat Tamm‐Horsfall glycoprotein (cTHP) was developed in order to investigate the possible role of cTHP in the pathogenesis of feline urolithiasis. Reproducible quantification required that the cTHP be disaggregated with 2M urea and 0.05% Tween 20. It was necessary to standardize rigidly the handling of the samples prior to analysis, since the apparent cTHP concentration varied depending on the preanalysis protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
3
10
0
1
Order By: Relevance
“…The amount of the HCl-soluble fraction of the urine was determined by subtracting HClinsoluble sediment from total sediment. Consistent with the results of previous studies [3,10], protein at 95-100 kDa was detected by SDS-PAGE only from urinary sediment (data not shown). In addition, this protein was further detected in the HCl-insoluble fraction of the sediment but not in the HCl-soluble fraction (data not shown), although it was expected in view of the extraction procedure.…”
supporting
confidence: 92%
“…The amount of the HCl-soluble fraction of the urine was determined by subtracting HClinsoluble sediment from total sediment. Consistent with the results of previous studies [3,10], protein at 95-100 kDa was detected by SDS-PAGE only from urinary sediment (data not shown). In addition, this protein was further detected in the HCl-insoluble fraction of the sediment but not in the HCl-soluble fraction (data not shown), although it was expected in view of the extraction procedure.…”
supporting
confidence: 92%
“…The HCl-soluble fraction consisted mainly of inorganic materials, whereas the HCl-insoluble fraction consisted mainly of organic materials [14]. Yamate et al [15] recently reported that the HCl-insoluble fraction contained an organic substance like Tamm-Horsfall glycoprotein, which was suggested to act as an organic matrix needed for the development of struvite urolith in cats [4,11].…”
mentioning
confidence: 99%
“…Because the HCl-insoluble fraction contains organic materials responsible for struvite urolith formation as a matrix [3,11,15], studies to explore the factors regulating the HCl-insoluble fraction would be necessary for the prevention of struvite urolithiasis. In the present study the HCl-insoluble fraction of urinary sediment tended to be higher in the CGM group than in the FM group (P<0.10), suggesting that the use of CGM as a major protein source may be a possible risk factor for struvite urolithiasis.…”
mentioning
confidence: 99%
“…The authors concluded that rate of THP synthesis was linked to neither the process of urine concentration nor the ion transport activity in the TAL. By using a similar method, urinary THP in cats was found to be 49.2 ± 35.5 ~tg/ml [22].…”
Section: Discussionmentioning
confidence: 97%